The Impact of a Pandemic on Children's Mental Health - Zumrotul Ula; Bernadetha Bernadetha; Nasrullah Nasrullah; Siti Utami Dewi; Ida Bagus Benny Surya Adi Pramana (Jurnal EduHealth, 2023)
The newly identified human infection caused by the coronavirus (SARS-CoV-2) is spreading rapidly around the world, posing a threat to population health and creating challenges to health systems. This disease, whose prognosis is unknown and uncertain with the scarcity of medical and personal protective equipment, has led to the implementation of measures limiting individual freedom. In addition to these factors, increased financial losses will contribute to widespread emotional distress and an increased risk of psychiatric disorders. This study aims to describe the psychological impact on children during the COVID-19 pandemic and identify solutions that can be provided for the data collection technique using the documentation method in the form of scientific journals published in national and international publishers on the internet. While the study of data analysis applied is the content analysis technique. The results of this study are 1) the psychological impact felt by elementary school-age children, which is most often mentioned, namely stress, then boredom and emotional instability, gadget addiction to depression, 2) the solution that can be given is that parents can involve children in household activities, Teachers can be expected to make the learning atmosphere enjoyable.